2019
DOI: 10.3390/v11030225
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Insights into Human Arboviral Infections: Dengue, Chikungunya, and Zika Viruses

Abstract: The global burden of arboviral diseases and the limited success in controlling them calls for innovative methods to understand arbovirus infections. Metabolomics has been applied to detect alterations in host physiology during infection. This approach relies on mass spectrometry or nuclear magnetic resonance spectroscopy to evaluate how perturbations in biological systems alter metabolic pathways, allowing for differentiation of closely related conditions. Because viruses heavily depend on host resources and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 137 publications
(356 reference statements)
1
32
1
Order By: Relevance
“…Surprisingly, only limited similarity was found in the metabolic profile between the two infected cell lines during the course of infection and in relation to uninfected cells. Thus, although it has been reported that viruses belonging to different families could cause some common metabolic responses [23,24], in our study it was observed that CrPV could induce only minimal common metabolic changes in different host cells.…”
Section: Discussioncontrasting
confidence: 69%
“…Surprisingly, only limited similarity was found in the metabolic profile between the two infected cell lines during the course of infection and in relation to uninfected cells. Thus, although it has been reported that viruses belonging to different families could cause some common metabolic responses [23,24], in our study it was observed that CrPV could induce only minimal common metabolic changes in different host cells.…”
Section: Discussioncontrasting
confidence: 69%
“…Viruses are obligate intracellular microorganisms that induce the reprograming of the host cell metabolism to support their own replication. This has been previously reported for various viruses, including HCMV [15], Middle East respiratory syndrome coronavirus (MERS-CoV) [16,17], adenovirus [18], dengue virus, and Zika virus [19]. For example, HCMV-infected cells display an increased dependence on glucose, and upregulate their glycolysis and lactate production.…”
Section: Discussionsupporting
confidence: 57%
“…This valuable information has unveiled potential antiviral targets that are now starting to be explored. It is expected that the detailed knowledge of the metabolic alterations (e.g., lipid metabolism) during ZIKV and other arboviral infections could help to design novel therapeutics, but also be useful to the identification of molecular biomarkers suitable for improved diagnostic [12]. This review summarizes the principal findings and the current status on the progress of the development of drugs that interfere with lipid metabolism and function as antivirals against ZIKV.…”
Section: Introductionmentioning
confidence: 99%